Individual Differences in Interoceptive Accuracy Are Correlated With Salience Network Connectivity in Older Adults - Ueno, Daisuke; Matsuoka, Teruyuki; Kato, Yuka; Ayani, Nobutaka; Maeda, Saaya; Takeda, Minato; Narumoto, Jin (Frontiers in Aging Neuroscience, 2020)
Interoceptive accuracy refers to the ability to consciously perceive the physical condition of the inner body, including one’s heartbeat. In younger adults, interoceptive accuracy is correlated with insular and orbitofrontal cortical connectivity within the salience network. As interoceptive accuracy and insular cortex volume are known to decrease with aging, we aimed to evaluate the correlation between salience network connectivity and interoceptive accuracy in older adults. Twenty-seven older adults (mean age, 77.29 years, SD = 6.24; 19 female) underwent resting-state functional magnetic resonance imaging, followed by a heartbeat counting task and neuropsychological test. We evaluated the correlation between interoceptive accuracy and salience network connectivity with age, sex, cognitive function, and total gray matter volume as covariates. Region of interest-to-region of interest analyses showed that interoceptive accuracy was positively correlated with the functional connectivity of the left rostral prefrontal cortex with the right insular, right orbitofrontal, and anterior cingulate cortices (F(6, 16) = 4.52, FDR-corrected p < .05). Moreover, interoceptive accuracy was negatively correlated to the functional connectivity of the left anterior insular cortex with right intra-calcarine and visual medial cortices (F(6, 16) = 2.04, FDR-corrected p < .10). These findings suggest that coordination between systems, with a positive correlation between left rostral prefrontal cortex and the salience network and a negative correlation between left insular cortex and vision-related exteroceptive brain regions, is important for maintaining interoceptive accuracy in older adults.